Pancreas insulary tumors producing insulin. Insulinoma.: About 3 cases. - Perrone, Luis; Silva, Celso; Chifflet, Juan; Botta, Fernando; Beltrán, Ricardo; Maggiolo, José; Bossano, Jorge; Petrucelli, Dante; Falconi, Luis (Cirugía del Uruguay, 1987)
Authors present three insulary adenomas (insulinomas) with clear neuroglucophenlc end digestive symptomatology and severa hypoglycemia crisis, certified by finding of glycemia and insulinemia by radioinmuno• logy. In only one case (Nº 3) a topographic diagnosis Presentado a la Sociedad de Cirugla del Uruguay el 14 de agosto de 1985. Prof. Adjunto Interino, Cirujano del Opto. de Emergencia. Prof. de Cllnica Quirúrgica, Prof. Adjunto de Cirugla Torácica, Residentes de Cirugla, Médico Endocrinólogo del M.S.P .. Ex-Prof. de Nefrologla, Ex-Asistente del Opto. de Anatomla Patológica. Dirección: Félix Laborde 2571. Montevideo (Dr. L Perrone). Instituto de Cirugla para Postgraduados. Hospital Pasteur, M.S.P. y Cllnica Quirúrgica "2" (Director Prof. Dr. Ce/so Silva). Hospital Maciel. Fac. de Medicina, Montevideo. was made by computerizeJ axial tomography and echo• graphy prior to operation. There was no arteriographic diagnosis in none of !he cases. Extemporaneous biopsy was positiva In two ca• ses. The three patients were treated by pancreatic resection with cure of hypoglicemia requiring insulin for a week and in another there appeared definitiva insulin• depending diabetes. lt is advisable to bé as conservativé as posible in the surgical removal, total panereatectomy being considered not nécessary. Among drugs, diazoxide is recomendad. No death occurred.